IMPROVING FINANCIAL AND MARKETING MANAGEMENT BASED DIGITAL APPLICATION ON SMEs BATIK TULIS INCUNG KERINCI - Ayu Esteka Sari; Zachari Abdallah; Ferry Siswadhi; Maryanto Maryanto; Gampo Haryono (Yayasan Education and Social Center, 2022)
The existence of MSMEs is essential to encourage the wheels of the nation's economy, so the government has to participate in the progress of SMEs. The fact found is that most of the MSMEs still do their financial records traditionally, and the level of awareness still needs to be higher on the importance of business financial statements. They are only armed with the knowledge and expertise they have, so they are still untouched by the media (application) tools in financial management. Likewise, with the implementation of marketing at the MSE. This activity aims to improve the ability of Batik Incung Subala SMEs actors to apply SI-APIK in managing financial reports and using digital marketing to promote their products. This activity resulted in that Batik Incung Subala can application the SI-APIK application in business financial management with continuous assistance and guidance and promoting products using digital marketing